1998
DOI: 10.1093/oxfordjournals.jbchem.a022243
|View full text |Cite
|
Sign up to set email alerts
|

Human Erythrocyte Bisphosphoglycerate Mutase: Inactivation by Glycation In Vivo and In Vitro

Abstract: 2,3-Bisphosphoglycerate mutase (BPGM) [EC 5.4.2.4] is a multifunctional enzyme that catalyzes both the synthesis and the degradation of 2,3-diphosphoglycerate (2,3-DPG) and contains three types of activities in that it functions as a 2,3-DPG synthetase, a phosphoglycerate mutase and a 2,3-DPG phosphatase. In humans, BPGM occurs only in erythrocytes and plays a pivotal role in the dissociation of oxygen from hemoglobin via 2,3-DPG. The present study shows that the specific activity of BPGM in erythrocytes of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 0 publications
0
11
1
Order By: Relevance
“…Previous studies have reported that oxidative stress can increase the glycosylation of proteins 6,8,9 . We hypothesized that hemoglobin glycosylation would be higher in pre‐term infants for two reasons: first, because certain prematurity‐associated complications mimic the effects of increased glycosylation of proteins; 2–5 and second, pre‐term infants have reduced levels of antioxidants and elevated levels of oxidative stress compared with those of full‐term infants, and oxidative stress can increase glycosylation 10–14 . The present study showed, however, that GHb levels were lower in pre‐term than full‐term infants.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Previous studies have reported that oxidative stress can increase the glycosylation of proteins 6,8,9 . We hypothesized that hemoglobin glycosylation would be higher in pre‐term infants for two reasons: first, because certain prematurity‐associated complications mimic the effects of increased glycosylation of proteins; 2–5 and second, pre‐term infants have reduced levels of antioxidants and elevated levels of oxidative stress compared with those of full‐term infants, and oxidative stress can increase glycosylation 10–14 . The present study showed, however, that GHb levels were lower in pre‐term than full‐term infants.…”
Section: Discussioncontrasting
confidence: 54%
“…Glycosylation of proteins in general can modify protein structure and alter catalytic properties, thereby causing cellular dysfunction in many organs 2 . For example, glycosylation of proteins can contribute to the development of retinopathy; and glycosylation of hemoglobin can alter oxygen dissociation, which influences tissue oxygenation and thus development of the fetus 2–5 . Glycohemoglobins (GHb) are the products of irreversible non‐enzymatic reactions between glucose and the hemoglobin molecule 6,7 .…”
mentioning
confidence: 99%
“…BCL2L1 (BCL-X), BNIP3L, and BAG1 are BCL2-associated proteins involved erythropoietin's known suppression of apoptosis during erythropoiesis (15). Other genes correlated with RDW are involved in the heme biosynthetic pathway (ALAS2) and in regulating hemoglobin oxygen affinity (BPGM) (16,17).…”
Section: Cellular and Physiological Themes In Gene Expression Variatimentioning
confidence: 99%
“…Amadori compounds such as fructosamines are formed during the early stage of glycation and represent the main products. This protein modification may lead to altered function, e.g., decreased activity of 2,3-bisphosphoglycerate mutase [1]. The two ketosamine kinases, fructosamine-3-kinase (FN3K) and fructosamine-3-kinase-related protein (FN3K-RP), can deglycate free and protein-bound Amadori compounds and are thus considered as protein repair enzymes [2].…”
Section: Introductionmentioning
confidence: 99%